UPAYA MENINGKATKAN EFIKASI DIRI MELALUI LAYANAN BIMBINGAN KONSELING - Nurfadhilla, Nona (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2020)
This article aims to look at how to improve self-efficacy through guidance and counseling services at SMP 1 Pleret, Yogyakarta. This type of research is qualitative descriptive, data collection methods through interviews and observations. Data analysis techniques using data reduction, data presentation and drawing conclusions. Results and discussion that there are still many students who have low self-efficacy so they are difficult to achieve good learning outcomes. This is proven by some students rarely doing school work and rarely doing homework also do not have the motivation to excel. BK teachers try through guidance and counseling services in the form of a preventive approach for those with high self-efficacy and a curative approach for students with low self-efficacy. Such as helping students to convince themselves that students are able to do tasks even though it is difficult and able to excel and to convince students to avoid feeling inferior about themselves. Guidance and counseling provided by BK teachers shows significant changes in some students who already have high self-efficacy. So it can be concluded that through guidance and counseling can be an effort to improve student self-efficacy.